2020
DOI: 10.17221/83/2020-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The use of genomic data and imputation methods in dairy cattle breeding

Abstract: The inclusion of animal genotype data has contributed to the development of genomic selection. Animals are selected not only based on pedigree and phenotypic data but also on the basis of information about their genotypes. Genomic information helps to increase the accuracy of selection of young animals and thus enables a reduction of the generation interval. Obtaining information about genotypes in the form of SNPs (single nucleotide polymorphisms) has led to the development of new chips for genotyping. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…SNP genotyping of animals can be done using biochips. These chips vary from lower density to higher density ( Klímová et al, 2020 ). Linkage disequilibrium (LD) between markers and QTL can better be captured using denser chips or panels ( Aliloo et al, 2018 ).…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…SNP genotyping of animals can be done using biochips. These chips vary from lower density to higher density ( Klímová et al, 2020 ). Linkage disequilibrium (LD) between markers and QTL can better be captured using denser chips or panels ( Aliloo et al, 2018 ).…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…Their findings provide evidence for the possible selection of dairy cows with a healthier milk FA composition by genomic selection schemes. Similarly, other authors have suggested a genomic approach to a complex description of the genetic background; this option helps to increase the chances of identifying loci associated with economically important traits [ 8 , 9 ]. The significant effect of FASN gene polymorphisms was also confirmed by other authors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%